A revisional study of the genus Aulacus Jurine (Hymenoptera: Aulacidae) of Japan - Kuroda, Keita; Konishi, Kazuhiko; Turrisi, Giuseppe Fabrizio; Yamasako, Junsuke (Zootaxa, 2020)
Japanese species of the genus Aulacus Jurine are revised and seven species are recognized. Two new species, A. davidi sp. n. and A. shizukii sp. n. are described. In addition, A. flavigenis Alekseev and A. sinensis He & Chen are newly recorded from the Japanese archipelago. Male genitalia of three species, i.e., A. davidi, A. flavigenis and A. sinensis, are described for the first time. An identification key for Japanese species and DNA barcoding data for A. davidi, A. machaerophorus Kuroda, Kikuchi & Konishi and A. sinensis are also provided.